2023
DOI: 10.1038/s41392-023-01620-3
|View full text |Cite
|
Sign up to set email alerts
|

The IL-17 family in diseases: from bench to bedside

Longjie Huangfu,
Ruiying Li,
Yamei Huang
et al.

Abstract: The interleukin-17 (IL-17) family comprises six members (IL-17A–17F), and recently, all of its related receptors have been discovered. IL-17 was first discovered approximately 30 years ago. Members of this family have various biological functions, including driving an inflammatory cascade during infections and autoimmune diseases, as well as boosting protective immunity against various pathogens. IL-17 is a highly versatile proinflammatory cytokine necessary for vital processes including host immune defenses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 338 publications
(373 reference statements)
1
17
0
Order By: Relevance
“…Higher levels of interleukin-17 (IL-17) secreting T lymphocytes was detected in blood and tonsillar mononuclear cells in ART patients. IL-17 is a family of cytokines involved with inflammatory conditions and is comprised of 6 subsets from IL-17A to IL-17F (8). IL-17C is functionally distinct from the rest of the family and is selectively induced in epithelial and germinal cells when exposed to bacterial stimulation (9), is upregulated early in infection (10), and is involved with maintaining the integrity of the epithelial barrier during infection (11).…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of interleukin-17 (IL-17) secreting T lymphocytes was detected in blood and tonsillar mononuclear cells in ART patients. IL-17 is a family of cytokines involved with inflammatory conditions and is comprised of 6 subsets from IL-17A to IL-17F (8). IL-17C is functionally distinct from the rest of the family and is selectively induced in epithelial and germinal cells when exposed to bacterial stimulation (9), is upregulated early in infection (10), and is involved with maintaining the integrity of the epithelial barrier during infection (11).…”
Section: Introductionmentioning
confidence: 99%
“…IL-17 is a universal cytokine in the TME that can induce the production of multiple factors, play a multifactorial role in tumour immunity, exert antitumour effects and promote tumour progression 30,31 . Abnormally elevated levels of IL-17 promote tumour progression by increasing cell proliferation and mutation rates and increasing immune tolerance in transformed cells 32 . Reppert et al performed qPCR on tissue samples from 25 NSCLC patients and reported that the expression of IL-17A was 10-fold greater in these patients than in healthy controls 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that chronic inflammation is a common phenomenon in different organs during the natural aging process. The TNF and IL-17 signaling pathways are involved in regulating metabolism and promoting an excessively inflammatory environment [ 74 , 75 ]. Moreover, beyond chronic inflammation, we also noticed that a large number of SASP genes were upregulated in both tissues.…”
Section: Discussionmentioning
confidence: 99%